Penyelenggaraan Pembangunan NKRI Menuju Negara Maritim Berdasarkan Prinsip Negara Kepulauan - Aryono Putra; Yasser Arafat (Universitas Borneo Tarakan, 2021)
ABSTRACT Indonesia has been deprived of its own true roots as a maritime country. This is the success of the colonial Dutch colonialists who do